Meet-and-Defer: The Rhetorical Unmaking of Graduate Academic Labor at the University of Maryland - DiBella, Samuel (Critical Education, 2025)
This small labor history studies the rhetoric and techniques used by administrators in the University System of Maryland to disperse and co-opt nascent graduate worker and adjunct unionization efforts in the 2010s. Those efforts centered on exploiting the strange social status of academic labor, claiming to speak for workers, and relying on the concept of university “shared governance” to create toothless advisory bodies. The success of that rhetoric, however, was contingent on intra-union conflict over turf and the inexperience of USM graduate organizers, who have continually directed their organizing efforts towards lobbying for state collective bargaining rights. USM’s rhetorical reframing of graduate academic labor contributed to the continuous defeat of graduate union drives in the USM for the last twenty years. This study suggests that efforts to change U.S. higher education through labor organizing should be wary of any attempt to channel organizing energy into bureaucratic bodies and that success will require an expansive definition of “shared governance” that includes graduate workers, adjuncts, and staff.